HUBUNGAN ANTARA AKTIVITAS FISIK DENGAN DURASI SIKLUS MENSTRUASI PADA REMAJA PEREMPUAN - Rahmania Delia Putri (2023)
Background: Based on RIKESDA (2018) the percentage of menstrual cycle disorders in young women aged 15-19 years in Indonesia is 11.7%. Menstrual Cycle Disorder can be caused by several factors, one of which is physical activity. The level of physical activity can affect the menstrual cycle. Physical activity can increase the body's metabolism which will help regulate levels of the hormones estrogen and progesterone which are useful for regulating the menstrual cycle. Physical activity can also increase endorphins levels, stabilize hormone levels and their effect on the hypothalamus-pituitary axis, increase oxygen supply to muscles which leads to an increase in the quality of the menstrual cycle. Purpose: This study was conducted to determine the relationship between physical activity and menstrual cycle length in young women. Methods: This study used a cross-sectional correlation research design with a total sample of 99 students from HASMI Islamic School. This study used IPAQ as a measure of physical activity and a questionnaire to determine the menstrual cycle. Results: It was found that the majority of the sample carried out moderate physical activity (57.6%) and normal menstrual cycles (68.7%). Based on statistical test data on the relationship between physical activity and menstrual cycle length, p=0.065 or p<0.05. Conclusion: The conclusion drawn from this study is that there is no significant relationship between physical activity and the length of the menstrual cycle.